Examining the Effect of Acceptance and Commitment Therapy on Self-Care and Treatment Adherence in Patients with Cardiovascular Diseases - Yekta, Mohammad Reza; Rahimi, Shadan; Gashool, Mohadeseh; Tahafpoor, Kimia; Hasoomi, Setareh (Mental Health and Lifestyle Journal, 2026)
The aim of the present study was to examine the effect of Acceptance and Commitment Therapy on increasing treatment adherence and improving self-care behaviors in patients with cardiovascular diseases. The present study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of patients with cardiovascular diseases who referred to medical centers in the city of Tehran in 2025. Sampling was conducted using a convenience method, and a total of 30 patients (15 in the experimental group and 15 in the control group) participated in the study. The experimental group received eight sessions of Acceptance and Commitment Therapy intervention. The research instruments included the Treatment Adherence Questionnaire and the Self-Care Questionnaire for Patients with Cardiovascular Diseases. Data were analyzed using descriptive statistics and repeated measures analysis of variance. The results indicated that after the intervention, treatment adherence and self-care scores in the experimental group increased significantly, whereas no significant change was observed in the control group (p < 0.05). The effect size showed that Acceptance and Commitment Therapy explained a substantial proportion of the variance in the dependent variables. Acceptance and Commitment Therapy led to increased treatment adherence and enhanced self-care behaviors in patients with cardiovascular diseases. These findings indicate the effectiveness of Acceptance and Commitment Therapy as a complementary psychological intervention in the management of patients with cardiovascular diseases and suggest its application in cardiac rehabilitation programs and comprehensive care.